2013
DOI: 10.1186/1471-2407-13-234
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of DNA double-strand break repair pathway genes and glioma susceptibility

Abstract: BackgroundGenetic variations in DNA double-strand break repair genes can influence the ability of a cell to repair damaged DNA and alter an individual’s susceptibility to cancer. We studied whether polymorphisms in DNA double-strand break repair genes are associated with an increased risk of glioma development.MethodsWe genotyped 10 potentially functional single nucleotide polymorphisms (SNPs) in 7 DNA double-strand break repair pathway genes (XRCC3, BRCA2, RAG1, XRCC5, LIG4, XRCC4 and ATM) in a case–control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…It is a DNA repair gene in nonhomologous end joining DNA repair pathway [24]. Genetic polymorphisms of XRCC5 were correlated with multiple cancers, including breast cancer, glioma, and hepatocellular carcinoma [25][26][27]. Up to date, there was no association studies reported between XRCC5 polymorphisms and lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…It is a DNA repair gene in nonhomologous end joining DNA repair pathway [24]. Genetic polymorphisms of XRCC5 were correlated with multiple cancers, including breast cancer, glioma, and hepatocellular carcinoma [25][26][27]. Up to date, there was no association studies reported between XRCC5 polymorphisms and lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, identification of novel genetic variants for assessing the early risk of glioma is attracting great interest across the global research community (Silva et al, 2013;Zhao et al, 2013;Hu et al, 2013). Based on genetic information, we may soon be able to determine the genetic etiology of glioma, identify high-risk individuals, and perform targeted therapy according to the genetic characteristics of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ATM-111 (G>A), a common functional SNP in the promoter region of the ATM gene, was reported to be a binding site of transcription factors that affect the ATM expression Zhang et al, 2010). Early epidemiological studies have identified ATM-111 (G>A) polymorphism as a strong risk factor in lung, breast, and oral cancers (Bau et al, 2010;Lo et al, 2010;Hsia et al, 2013;Zhao et al, 2013;Liu et al, 2014). However, inconsistent results were reported in thyroid cancer, leukemia, and other cancers (Pharoah et al, 2007;Zhao et al, 2013;Damiola et al, 2014;Song et al, 2015).…”
Section: Introductionmentioning
confidence: 97%